2011
DOI: 10.1002/hed.21897
|View full text |Cite
|
Sign up to set email alerts
|

Impact of comorbidity on therapeutic decision‐making in head and neck cancer: Audit from a comprehensive cancer center in India

Abstract: Comorbidity in patients with head and neck cancer can influence therapeutic decision-making. Prospective longitudinal rigorous collection of comorbidity data is warranted for correlation with outcomes. ACE-27 may be a clinically more meaningful tool for comorbidity assessment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 26 publications
(36 citation statements)
references
References 19 publications
4
32
0
Order By: Relevance
“…3 Approximately, one fifth of the patient population had moderate to severe comorbidity, a prevalence rate similar to that reported by Piccirrilo et al 12 Overall, our study demonstrates that a higher grade of comorbidity predicts for greater deviation from an ideal treatment plan, which in turn results in a suboptimal outcomes. Nearly two thirds of the patient population in current study had some comorbidity which is higher than that reported in our previous study.…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…3 Approximately, one fifth of the patient population had moderate to severe comorbidity, a prevalence rate similar to that reported by Piccirrilo et al 12 Overall, our study demonstrates that a higher grade of comorbidity predicts for greater deviation from an ideal treatment plan, which in turn results in a suboptimal outcomes. Nearly two thirds of the patient population in current study had some comorbidity which is higher than that reported in our previous study.…”
Section: Discussionsupporting
confidence: 85%
“…3 The reasons for deviation from the ideal treatment plan were noted in the CRF. 3 The reasons for deviation from the ideal treatment plan were noted in the CRF.…”
Section: Study Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…Comorbidity is an infrequently reported variable in either large‐scale clinical trials comparing different treatment arms or in registry‐based studies exploring outcome trends, however, our study supports emerging literature citing its importance . The comprehensive ACE‐27 score used in this study includes 27 variables graded by severity, including alcohol use, cardiorespiratory disease, and previous/concurrent carcinomas.…”
Section: Discussionsupporting
confidence: 70%
“…If there is agreement upon anything, it is that personalized treatment incorporating both patient and tumor variables is likely to yield optimal survival and functional outcomes . This is particularly pertinent in a patient population with a high burden of smoking and alcohol‐associated comorbidities, which may influence treatment options and survival . Second, laryngeal function, rather than conservation alone, is recognized as an important yet infrequently studied outcome in its own right .…”
Section: Introductionmentioning
confidence: 99%